PEMBERDAYAAN REMAJA MASJID ATTAQWA DARUSSALAM SEBAGAI UPAYA PENINGKATAN LITERASI DIGITAL MASYARAKAT - wardani, Setia; Muhfizaturrahmah; Gilang Jiwana (DHARMA BAKTI, 2023)
Partners in the Community Partnership Program (PKM) are Attaqwa Darussalam Mosque Youth, Klenggukan Pundang Tirtomartani Kalasan. The partners' main problems are digital literacy knowledge and low utilization of Information and Communication Technology (ICT). The purpose of PKM is to provide reinforcement to mosque youth regarding digital literacy, assistance in website development and management. The solution to overcome problems with partners is through training methods including (1) Operation and maintenance of ICT equipment 2) Digital literacy which includes efficient searching and internet safety, 3) Positive content creator through personal blogs and social media. Furthermore, the PKM Team also provides assistance so that target partners are able to develop positive content through 4) Website design that is informative, attractive and up to date. The result of this PKM is an increase in digital literacy knowledge in mosque youth, the website of the Attaqwa Darussalam mosque is www.masjid.klenggukan.com.